INVENÇÃO DE ORFEU: UMA EPOPÉIA MODERNA? - Sterzi, Eduardo (Organon, 2012)
Jorge de Lima’s masterpiece, Invenção de Orfeu, was misunderstoodand misjudged by some readers as Mário Faustino - who, notwithstanding, thoughtof Jorge de Lima as “the greatest name in our poetry” - and Augusto and Haroldo deCampos. The problems of the work, as signalized by Faustino and the Campos, couldbe summarized in two topics: absence of unity (orstructure) and indefinition of genre. These reproaches, however, seem to forget poet’sexplicit intention to proceed the “modernization of epic”.